MAIN DIRECTIONS OF PROVIDING HIGHLY QUALIFIED PERSONNEL ON THE BASIS OF THE INTEGRATION OF HIGHER EDUCATION AND THE LABOR MARKET (Marketing Journal, 2025)
This article provides an in -depth analysis of the integration between higher education and the labor market in Uzbekistan, with a focus on regional characteristics of the Kashkadarya region. Using statistical indicators, the study examines graduate employa bility, the level of practical training, and skill mismatches. Drawing on international best practices from Germany, South Korea, and the United States, the paper proposes strategic directions for improving labor market responsiveness of higher education i n Uzbekistan. The findings reveal the necessity to expand dual education models and enhance digital and practical skills.
Keywords: higher education; labor market; integration; dual education; skill mismatch; employability; Kashkadarya № 10-SON OKTA BR; 2025 -YIL 337